PENGARUH HARGA BBM TERHADAP INFLASI DI JAWA TIMUR - Puspsosari, Luthfiya Fathi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The aim of this study is to describe how much influence the fuel price (the price of petrol and diesel prices) on Inflation in East Java-year period 2000-2015. This type of research is explanatory research with quantitative approach. The research data include the price of fuel (gasoline) at 2000 to 2015, the fuel price (Solar) at 2000-2015 and Inflation rate at 2000-2015 in East Java. Analysis of the results of research using Multiple Linear Regression. Results showed that the price of gasoline partially significant effect on inflation in East Java, but the price of diesel fuel does not influence significantly on inflation in East Java. Fuel price includes the price of gasoline and diesel prices affect the simultaneous inflation in East Java, meaning that one of the factors that caused a inflation in East Java affected by changes in the price of gasoline and diesel prices.Keywords: Price of Fuel (Gasoline and Solar), Inflation and East Jawa